Two Cases of Interleukin-7–Deficient Generalized Verrucosis. (4th January 2020) - Kosumi, Hideyuki; Natsuga, Ken; Takashima, Shota; Miyauchi, Toshinari; Huang, Yi-Ting; Nomura, Toshifumi; Yanagi, Teruki; Huang, Hsin-Yu; Chiu, Frank Po-Chao; Chen, Peng-Chieh; Hsu, Chao-Kai; Shimizu, Hiroshi
Abstract: We report 2 generalized verrucosis (GV) patients homozygous for a novel mutation in the start codon of IL7 . Unlike the previous report in which IL-7 deficiency accompanied CD4 T lymphocytopenia, circulating CD4 T cells were not depleted in one of our patients, suggesting a GV pathogenesis other than poor T-cell development.